The Phases of Hahnemann's Medical Practice - Morrell, Peter (Homœopathic Links, 2021)
Using data from his casebooks, this study explores the medical practice of Hahnemann with a focus on his changing use of medicines and potency. This study also identifies several phases in his use of medicines that connect with his ongoing programme of new provings. This study also reveals that only when he had chanced upon the antipsoric medicines, he did stop changing his medicines. Similarly, data taken from the casebooks reveal changes in his use of potency and the development of his unique method of preparing medicines as he experimented with higher and higher potencies as his career progressed.
Keywords: Hahnemann; potency; history; provings; medicines